The Effect of corporate culture on organizational performance: a case of Basecamp Explorer Kenya - Katieno, G. (Strathmore University, 2025)
The study explored how organizational culture affects performance following a corporate merger, using Basecamp Explorer - a tourism company formed from the merger of Basecamp Explorer Kenya and Old Boma Ltd - as the case study. The research was anchored in the Competing Values Framework (CVF) and the Balanced Scorecard (BSC), offering a comprehensive model for analyzing both culture and performance. The study sought to: (1) assess the impact of Clan Culture on performance; (2) explore how Adhocracy Culture influences outcomes; (3) evaluate the role of Market Culture; and (4) examine the effects of Hierarchical Culture. A quantitative methodology was adopted, with data collected through structured questionnaires completed by 152 employees from diverse departments and roles at Basecamp Explorer. Descriptive statistics were used to outline respondent characteristics and summarize the cultural dimensions, while regression analysis examined the relationships between different culture types and organizational performance. The analysis showed that Clan and Adhocracy Cultures significantly contributed to enhanced collaboration, innovation, and customer satisfaction. Market Culture was strongly associated with achieving goals and maintaining a competitive edge. Conversely, Hierarchical Culture promoted order and control but was seen as restricting adaptability and creativity. The findings offer strategic insights for Basecamp Explorer and similar firms undergoing post-merger transitions, emphasizing the value of fostering team-oriented, innovative, and performance-driven cultures to boost success. Keywords: Organizational Culture, Organizational Performance, Competing Values Framework, Balanced Scorecard, Post-Merger Integration, Tourism Industry, Kenya.
Full - text thesis